User requirements assessment of the community health information tracking system implications for digital preservation - Trinidad, Daryll O., 1994-
Electronic Medical Records hold highly important and confidential information. Thus, it is necessary that these records are kept in a trustworthy repository set in a sustainable environment to ensure its preservation for the long term. This study focused on the assessment of the organizational infrastructure of healthcare units equipped with Community Health Information Tracking System (CHITS) using the Trustworthy Digital Repository Checklist as tool to evaluate its current work processes and its readiness on the long-term preservation of Electronic Medical Records.